The Relationship between Regiousity and Family Support with Meaningfulness of Life of Chronic Kidney Failure’s Clients in Curup Hospital - Mulyadi Mulyadi; Almaini Almaini (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Basic medical research 2013 pointed to an increasing prevalence GGK by province in Indonesia in 2013, interviews doctor's diagnosis increases with age, the rose sharply in the age group 35-44 years (0.3%), was followed the age of 45-54 years (0.4%) and aged 55-74 years (0.5%) is the highest in the age group 75 years (0.6%). The study aims to know the relationship religiousity and family support to the meaningfulness life of patients with chronic renal failure undergoing hemodialysis. Design Analytical research using descriptive method with cross sectional approach. Samples are renal failure patients undergoing hemodialysis in hospitals Curup is counted many as 56 people. The results showed there significant relationship between religiutitas and family support to the meaningfulness life of patients. By increasing religiutitas family support will increase the motivation of patients in hemodialysis therapy. Keywords : CRF, haemodialysis, meaningfulness life, religiousity